1948
DOI: 10.1002/pol.1948.120030307
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide as catalyst for emulsion polymerization of butadiene and styrene

Abstract: Evidence is presented to show that either sodium ferri‐ or ferropyrophosphate with hydrogen peroxide effectively initiates emulsion copolymerization of butadiene and styrene. The hydrogen peroxide appears to be destroyed as such before polymerization begins, thus indicating that it converts some other constituent of the recipe into the effective catalyst for polymerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1949
1949
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…In the modifying range of dodecyl mercaptan concentrations the plasticity of GR-S can be varied widely from stiff polymers of a Mooney plasticity value of 150 to very soft polymers of about 15 Mooney. Polymers of about 50 Mooney plasticity are most satisfactory for factory processing.…”
Section: Initiation and Modificationmentioning
confidence: 99%
“…In the modifying range of dodecyl mercaptan concentrations the plasticity of GR-S can be varied widely from stiff polymers of a Mooney plasticity value of 150 to very soft polymers of about 15 Mooney. Polymers of about 50 Mooney plasticity are most satisfactory for factory processing.…”
Section: Initiation and Modificationmentioning
confidence: 99%
“…(35) showed that a water solublc l~eroxide such as hydrogen peroxide disappeared from the ~nedium prior t o polymerization. Ho~~rever, the work published by Fordham and Williams (5,6,7,8,9), by Icharasch et al (22,23) and by I<olthoff et al (24,28,30) str-ongly suggested that the most probable locus of initial free radical fornlation was in the aqueous phase.…”
Section: Caivadian Journal Of C H E X I S T R Y 10lmentioning
confidence: 99%
“…Johanson and Goldblatt (88) review the effect of catalysts and modifiers on the yield, solubility, and viscosity of copolymers obtained by the emulsion polymerization of isoprene and styrene. The use of hydrogen peroxide as a catalyst for the emulsion copolymerization of butadiene and styrene was studied by Marvel, Deanin, Claus, Wyld, and Seitz (114). Redington (137) reports on the effectiveness of various diacyl peroxides as catalysts for the bulk polymerization of styrene.…”
Section: Catalysts Modifiers and Inhibitorsmentioning
confidence: 99%
“…Chem., 41, 992-1003 (1949). (114) Sherwood, P. W., Petroleum Processing, 28, 129-34 (1949). ( 115) Simonds, J. H. (to Phillips Petroleum Co.), U. S. Patent 2,458,-107 (Jan. 4,1949).…”
mentioning
confidence: 99%